On retail digital platforms suppliers have to become responsive customer service organizations. Issue 1 (20th December 2018) - Hänninen, Mikko; Smedlund, Anssi
Abstract : Purpose: We illustrate how multi-sided retail marketplaces enabled by a digital platform, engage suppliers, creating new rules of retail altogether. Specifically, we describe how these marketplaces create relational value for their suppliers, as through marketplaces like Amazon.com, suppliers are fully integrated members of the value-exchange relationship with the platform's end-customers. Design/methodology/approach: This paper is the result of a study of three leading marketplaces. We compared the marketplaces to understand the impact of the platform economy on the retail industry, including on the governance mechanisms and earnings logic. We identified supplier management as a key theme in our analysis, as on marketplaces such as Amazon.com, the management of supplier relationships differs from more traditional forms of retail, as in platforms, supplier quality reflects strongly on the reputation and reliability of the marketplace. Findings: Our findings show that in addition to well-known customer engagement processes, the marketplaces also have supplier engagement processes in-place. Through engagement processes, marketplaces are able to lock-in suppliers, thus increasing the total value of the marketplace. For suppliers, marketplaces create relational value, in an industry where competition has traditionally centered on price, selection and location. Originality/value: Thus far, studies have shown that companies differentiate through customer engagement. This paper looks at the same phenomena from the supplier side. We contribute to the understanding of complementor management in the platform economy. Based on our study, we expect that the novel concept of supplier engagement will transform how retailers interact with suppliers.